Surgical Management of Lumbar Spinal Stenosis; Analysis of Pre- Operative Risk Factors Affecting Outcome (Journal of Pakistan Orthopaedic Association, 2015)
Objective: To evaluate pre-operative risk factors have impact upon post-operative outcome in terms of pain and functional improvement after surgical decompression of lumbar spinal stenosis.Methods: Retrospective analysis of prospectively data was collected for LSS patients from backache care service until 6 months post-operatively. Neurological and medical factors were identified and were assessed in terms of post-operative improvement in VAS pain scores as well as ODI functional improvement.Results: Forty five patients were included with 62.2%(n=28) males & 37.8%(n=17) females. Mean age was 61.98 years ± 7.06 SD (range: 47-75 years). Mean duration of symptoms was 27.11 years ± 8.88 SD, 80% of patients achieved effective pain relief and favourable functional improvement. The pre-operative risk factors included tobacco use (24.4%), mostly in the form of ‘Naswar’. Comorbid conditions were present in 46.7% patients and included diabetes (15.6%), hypertension (11.1%) and osteoarthritis (8.9%), 13.3% patients had history of previous spine surgery, mostly for prolapsed lumbar intervertebral disc. Surgery was significantly associated with improvement between pre- & post-operative pain scores and ODI scores (p < 0.001). Tobacco use was significantly associated with poor pain functional improvement (p = 0.001). No association was found for gender (p = 0.64), age (p = 0.094), comorbids (p = 0.88), duration of symptoms (p = 0.67) or previous surgery (p = 0.82) for predicting post-operative prognosis.Conclusion: Surgical intervention is a good choice in relieving pain and disability due to lumbar spinal stenosis. Tobacco use is a risk factor strongly associated with poor outcomes.Keywords: Lumbar spinal stenosis, laminectomy, surgical outcome, pre-operative risk factors.Abbreviations: LSS: lumbar spinal stenosis, EPR: Effective pain relief, ODI: Oswestry disability index, VAS: Visual analogue scale